Content and Radio Broadcast Innovation at RRI Sumenep in the Digital Era - Rizqi Elmalia (Penerbit Hellow Pustaka, 2026)
This research aims to examine the innovation of broadcast content carried out by Radio Republik Indonesia (RRI) Sumenep in responding to challenges and opportunities in the digital era. In the face of changes in media consumption patterns that are increasingly leading to digital platforms, public broadcasting institutions such as RRI are required to transform to remain relevant and reach a wider audience, especially the younger generation. This study uses a descriptive qualitative approach with a case study method in RRI Sumenep. Data collection techniques are carried out through in-depth interviews, participatory observations, and documentation of broadcast programs and digitalization strategies implemented. The results of the study show that RRI Sumenep has carried out various content innovations, such as the integration of conventional broadcasts with social media, the development of podcasts based on local wisdom, and the optimization of streaming platforms to expand the reach of the audience. These innovations are not only.